2021
DOI: 10.1155/2021/7239291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Leea rubra Leaf Extract for Oxidative Damage Protection and Antitumor and Antimicrobial Potential

Abstract: Background. The leaves of Leea rubra contain an abundance of phenolic constituents and have medicinal uses as antipyretic and diaphoretic agents and are also used in the treatment of stomach ache, rheumatism, arthritis etc. In spite of the traditional uses, data on the scientific evaluation of the plant are not sufficient. So, the present study was designed to evaluate the protective role of the extract against oxidative damage to DNA and human erythrocytes as well as antitumor and antibacterial activities aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Scientific evidence efforts showed that L. rubra had several pharmacological activities, including antioxidant, anticancer, and antibacterial (Das et al, 2021) (Kadchumsang et al, 2014). The results of other studies showed that this plant also had the potential to be developed as a functional food source.…”
Section: Leea Rubramentioning
confidence: 99%
“…Scientific evidence efforts showed that L. rubra had several pharmacological activities, including antioxidant, anticancer, and antibacterial (Das et al, 2021) (Kadchumsang et al, 2014). The results of other studies showed that this plant also had the potential to be developed as a functional food source.…”
Section: Leea Rubramentioning
confidence: 99%
“…It also has effectiveness against bronchitis, fever, itching and snake bites. But only antimicrobial and anti-inflammatory activities were reported from L. rubra in recent study [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%